UNIT 11.15 In Vivo Electrophysiological Recording Techniques for the Study of Neuropathic Pain in Rodent Models. Issue 1 (2nd September 2014) - Zhao, Fei‐Yue; Jeggo, Ross; Wei, Haifeng; Whyment, Andrew; Fang, Xin; Spanswick, David
Abstract: Neuropathic pain develops following nerve injury, and is a chronic pain syndrome that can persist long after repair of a wound or removal of the neurological insult. This condition remains poorly treated, not least because of a lack of mechanism‐based therapeutics. Clinically, neuropathic pain is characterized by three major symptoms: thermal or mechanical allodynia (pain sensation in response to previously non‐noxious stimuli); hyperalgesia (enhanced pain sensation to noxious stimulation); and spontaneous, ongoing pain. These clinical symptoms can be modeled in rodent neuropathic pain models using behavioral and electrophysiological readouts. This unit describes techniques designed to record pathophysiological electrical activity associated with neuropathic pain at the level of the periphery, in single fibers of primary sensory neurons, and from wide dynamic range (WDR) neurons of the dorsal horn of the spinal cord. These techniques can be employed in both naïve animals and in animal models of neuropathy to investigate fundamental mechanisms contributing to the neuropathic pain state and the site, mode, and mechanism of action of putative analgesics. Curr. Protoc. Pharmacol . 66:11.15.1‐11.15.26. © 2014 by John Wiley & Sons, Inc.